Influência do Uniconazole no crescimento e desenvolvimento da planta na composição química de grãos de milho - Dembocurski, Diogo (2023)
This work aimed to evaluate the effect of biostimulants, including Uniconazole (UCZ), to verify corn hybrids' responses in their development stages. First, a preliminary experiment was performed to verify the maximum dose (EXP1) of UCZ (0, 50, 100, and 150 mg kg-1 of seed), and a dose of 200 mg Kg-1 was included in a complementary experiment (EXP2). These experiments were conducted in the laboratory for germination tests by treating seeds of hybrid MSG1001 with UCZ, inserted in germination paper, and incubated in BOD at 25ºC with 12h photoperiod for one week. The experimental design was entirely randomized with four repetitions. An accelerated aging test (EXP3) was performed to check seed vigor, in which the seeds were initially treated with UCZ (0, 50, 100, 150, and 200 mg kg-1 seed). Afterward, the seeds were distributed in aluminum screens placed on germination boxes containing distilled water and then incubated in a BOD-type germination chamber (72h at 45ºC). After the incubation period, a new germination test was performed. An experiment was implemented and conducted to evaluate the initial development of the hybrid up to the V4 stage (EXP4), in which the plants from seeds previously treated with UCZ (0 to 200 mg kg-1 seed) were grown in pots containing medium sand using localized irrigation and nutrient solution. The experimental design was entirely randomized with eight repetitions. For the experiment under field conditions (EXP5), seeds treated with UCZ and Azospirillum brasilense (AZP) were sown in previously furrowed and fertilized soil. At the V6 stage, different doses of sodium selenate (SS) were applied by knapsack spraying. The experimental design was randomized blocks in a trifactor scheme with four repetitions: Uniconazole (0, 50, 100, and 150 mg kg 1 seed); Azospirillum brasilense (0 and 100 ml sc-1 seed); Selenium (0, 25, and 50 g ha-1 ). The results obtained in EXP1 showed that UCZ promoted a reduction in average seedling and root length without decreasing the germination percentage. With the addition dose (EXP2), by regression analysis, it was found that there was a reduction in the germination percentage at seven days. No change in germination percentage was detected to evaluate seed vigor (EXP3), but a negative linear regression was detected in seedling size and aboveground biomass as the dose of UCZ increased. Plants grown in pots with sand (EXP4) showed a reduction in size starting at 50 mg UCZ until eight days after planting (DAP), and, at 12 DAP, a 32% reduction in size was observed at 200 mg UCZ, when compared to the control, which delayed their initial growth, not being detected at 20 DAP. The analysis of root morphology by imaging showed an increase in length and root area with a reduction in diameter as the dose of UCZ increased. Leaf tissue analysis found that UCZ promotes an increase in photosynthetic pigments and an increase in light absorption capacity in the visible region. Moreover, it was found that the mineral composition of the plants is modified according to the dose of UCZ. Plants grown in the field with the application of Uniconazole, Azospirillum brasilense, and selenium (EXP5) had no effects on plant growth and yield of the hybrid but showed modifications in crude fiber contents and mass of one thousand grains. It was concluded that UCZ promotes retardation of the germination process. As the dose increases, there is a reduction of growth in its initial phase; it also promotes modification in the root system, which may increase the capacity to absorb water and nutrients. UCZ influences the plant's photosynthetic capacity, improving its light absorption in the visible region. By combining UCZ, AZP, and SS, it was concluded that there was an increase in the yield components mass of one thousand grains